Mathematics in the modern world - Reyes, Juan Apolinario C. (Manila : Unlimited Books Library Services & Publishing , Inc., 2023)
"This book is supported by Great Deeds Academy, a YouTube video channel devoted to mathematics. While keeping an eye on the guidelines set by CHED, we exercised our discretion so that the cost of producing this book is not going to be very expensive. We did this by focusing only on topics that are within the teaching competence of many math teachers in the collegiate level. In the interest of reducing the cost of publishing and maximizing the use of the book, Mathematics in the Modern World is divided into the following chapters: 1) nature of mathematics; 2) data management; 3) mathematics of finance; 4) logic and symbolic argument; and 5) cryptography."
Includes references.
English.
Keywords: Mathematics